Kritik Sosial Melalui Wacana Kritis pada Puisi Esai Mata Luka Sengkon Karta - Andre Bastian; Mohamad Karmin Baruadi; Herman Didipu (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Norman Faircloughs critical discourse analysis aims to reveal the message of social criticism in the essay poetry of Mata Luka Sengkon Karta by Peri Sandi Huizche through text structure, discourse practice, and sociocultural practice. The research method is descriptive qualitative. The results of the research and discussion illustrate that the message of criticism is through individual, group and group to group social interaction. Discourse practices in the form of murder and robbery. Situational socio-cultural practices which include motives, and institutional which include mass media organizations, and socio-cultural which include togetherness, nationalist, moral and religious values. The prominent social criticisms are poverty, crime, law enforcement, and discrimination.